An environmentally friendly electrochemical reactor for the degradation of organic pollutants in the total absence of a liquid electrolyte: A case study using diclofenac as a model pollutant. Issue 4 (August 2017) - Faria, Emanuel R.; Ribeiro, Fernando M.; Verly, Rodrigo M.; Franco, Débora V.; Da Silva, Leonardo M.
Graphical abstract: Highlights: An environmentally friendly SPE reactor for the degradation of organic pollutants. The anode composition did not affect the degradation of diclofenac. The contaminated water can be treat in the absence of a liquid electrolyte. Abstract: In order to fabricate an environmentally friendly electrochemical reactor for the degradation of organic pollutants in the total absence of a liquid electrolyte, fluid-permeable anodes (FPAs) composed of mixed oxide-covered mesh electrodes (MOMEs) containing cobalt and nickel, denoted as MOME-Ni( x ) Co(1− x ) O y where x  = 0.9, 0.8 and 0.3, were prepared by thermal decomposition using the slow cooling rate method on a stainless-steel fine-mesh support. The electrochemical degradation of diclofenac (model pollutant) in electrolyte-free water was carried out in batch mode using a solid polymer electrolyte (SPE) electrochemical reactor. For the different MOME compositions, their properties were investigated as a function of the initial drug concentration (IDC) and the electric current density ( j ). The effects of IDC and j on the degradation of diclofenac were quite similar according to analyses performed using UV–vis and HPLC techniques, wherein it was verified for the different MOMEs that the degradation rate of diclofenac increased with increasing j and IDC. The electrode composition (Ni percentage) exerted only a minor influence on the degradation of diclofenac. On the other hand, a strong influence of j and IDC on the degradation was verified. It was also verified that an increase in IDC resulted in higher values of total current efficiency (TCE) measured for the combustion reaction. Taking into account that the lowest values of the electrical energy per order ( E EO ) were obtained for MOME-Ni(0.3) Co(0.7) O y, it was concluded that the best overall performance for the electrochemical degradation of diclofenac in electrolyte-free water was achieved using this electrode composition.